The magic boomerang - MacPherson, Bruce; MacPherson, June.; Ratcliffe, Merla (Sydney : Horwitz, 1970)
Childrens story at Ayers Rock.
"An enchanting story of the great outback - photographed in colourful Central Australia." - cover.
Childrens book (age 5-7); illus.; (pt col.)
Muir, M. A bibliography of Australian children's books
For children.
Keywords: Adventure stories, Australian; Children's stories, Australian; Northern Territory -- Juvenile fiction; Uluru/Ayers Rock (N.T.) -- Juvenile fiction; Literature and stories - Juvenile; Stories and motifs - Weapons - Boomerangs; Uluru / Ayers Rock (South Central NT SG52-08)